2012
DOI: 10.1001/archpediatrics.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholecalciferol as Adjunctive Therapy With Insulin on Protective Immunologic Profile and Decline of Residual β-Cell Function in New-Onset Type 1 Diabetes Mellitus

Abstract: To evaluate the effect of vitamin D 3 on cytokine levels, regulatory T cells, and residual ␤-cell function decline when cholecalciferol (vitamin D 3 administered therapeutically) is given as adjunctive therapy with insulin in new-onset type 1 diabetes mellitus (T1DM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
118
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 53 publications
8
118
2
5
Order By: Relevance
“…The cumulative incidence of progression to undetectable fasting C-peptide level reached 18.7% in the cholecalciferol group and 62.5% in the placebo group. Therefore, cholecalciferol is safely used as an adjunctive therapy with insulin and is associated with protective immunological effects and a slow decline in the function of residual β -cells in patients with T1DM [30]. A study of patients aged 18 -39 years in Germany who was newly diagnosed with T1DM who received 0.25 µg 1.25(OH) 2 D 3 or placebo daily for 9 months and followed for a total of 18 months.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…The cumulative incidence of progression to undetectable fasting C-peptide level reached 18.7% in the cholecalciferol group and 62.5% in the placebo group. Therefore, cholecalciferol is safely used as an adjunctive therapy with insulin and is associated with protective immunological effects and a slow decline in the function of residual β -cells in patients with T1DM [30]. A study of patients aged 18 -39 years in Germany who was newly diagnosed with T1DM who received 0.25 µg 1.25(OH) 2 D 3 or placebo daily for 9 months and followed for a total of 18 months.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…The dose of cholecalciferol used should be such that is able to achieve optimal serum vitamin D concentrations (40-60 ng/mL) required to produce immunomodulatory effects. In previous studies, higher vitamin D concentrations ([60 ng/mL) were shown to increase the number as well as functions of Tregs [3,4]. Thus, the cholecalciferol dose of 2000 IU/day may need to be increased in future studies, particularly in certain patient populations [11].…”
mentioning
confidence: 98%
“…In previous studies, the protective effects of vitamin D on RBCF were better in patients with higher C-peptide concentrations at inclusion [3,9] than in those with lower baseline C-peptide [6,7]. The dose of cholecalciferol used should be such that is able to achieve optimal serum vitamin D concentrations (40-60 ng/mL) required to produce immunomodulatory effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations